2018
DOI: 10.35454/rncm.v1n1.075
|View full text |Cite
|
Sign up to set email alerts
|

Concordancia-conformidad entre los dinamómetros de mano Camry y Jamar en adultos

Abstract: tiene utilidad en la práctica médica. Actualmente no existe un dinamómetro validado en población colombiana. Objetivo: determinar la concordancia-conformidad del dinamómetro Camry en una población de adultos colombianos de 18 a 59 años. Métodos: estudio transversal de concordancia, en hombres y mujeres de la comunidad universitaria entre 18 a 59 años de edad. Se midieron variables demográficas, de salud y antropométricas. La concordancia de los dinamómetros se evaluó con el coeficiente de correlación-concordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Presently, the Jamar dynamometer is the most common device utilized and recommended for measuring grip strength as compared to the Collin dynamometer, because its use could be more precise, as it facilitates grip and use of force [ 50 ]. Nevertheless, close values have been obtained ( r > 0.8; p < 0.001) between the use of the Jamar and Camry dynamometers, with the use of the latter being adequate for medical use [ 69 ]. Despite the lack of previous studies on the intra-rater reliability with the Camry dynamometer, the high test–retest correlation obtained in the present study coincides with the study by Hogrel [ 70 ], in which an excellent reliability was demonstrated (ICC = 0.967) using an electronic manual dynamometer (Myogrip; Ateliers Laumonier, France), which is very similar to the Camry dynamometer.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the Jamar dynamometer is the most common device utilized and recommended for measuring grip strength as compared to the Collin dynamometer, because its use could be more precise, as it facilitates grip and use of force [ 50 ]. Nevertheless, close values have been obtained ( r > 0.8; p < 0.001) between the use of the Jamar and Camry dynamometers, with the use of the latter being adequate for medical use [ 69 ]. Despite the lack of previous studies on the intra-rater reliability with the Camry dynamometer, the high test–retest correlation obtained in the present study coincides with the study by Hogrel [ 70 ], in which an excellent reliability was demonstrated (ICC = 0.967) using an electronic manual dynamometer (Myogrip; Ateliers Laumonier, France), which is very similar to the Camry dynamometer.…”
Section: Discussionmentioning
confidence: 99%
“…La fuerza de agarre manual se evaluó utilizando un dinamómetro (Camry Model EH101) y las puntuaciones se registraron en kilogramos, los participantes ejecutaron la prueba según las instrucciones de la sociedad americana de terapeutas de mano, se realizaron tres intentos con la mano dominante con un minuto de descanso entre series y se obtuvo el mejor valor para el análisis [42].…”
Section: Fuerza De Agarre Manualunclassified